Cover Feature: Selective Enhancement of Electrochemical Signal Based on the Size of Alcohols Using Nanoporous Platinum (ChemElectroChem 13/2021). Issue 13 (2nd June 2021) - Bang, Jae Jin; Han, Donghoon; Shin, Jinsik; Chung, Taek Dong; Bae, Je Hyun
Abstract : The Cover Feature illustrates selective enhancement of methanol electrooxidation in the ultra‐compact nanoporous Pt electrode. Methanol is smaller than 1‐propanol so that it can penetrate deeper into the nanopores. It is essential to consider the size of the reactive species at nanoporous electrodes. More information can be found in the Communication by J. J. Bang et al .